Effectiveness of specific muscle group stretching in reducing regional musculoskeletal disorders among textile workers (International Journal of Occupational Safety and Health, 2025)
Introduction: Regional musculoskeletal disorders (MSDs) are prevalent in the textile industry, primarily due to repetitive or static work postures. This study aimed to assess whether specific muscle group stretching exercises could reduce MSDs complaints among workers in the textile industry.Methods: A quasi-experimental design with a pretest–posttest approach without a control group, which limits causal inference, was employed. Thirty textile workers participated in a structured stretching program twice daily for 8 weeks. Complaints of MSDs were assessed using the Nordic Body Map (NBM) questionnaire at baseline, Week 4, and Week 8. The data were analyzed using Repeated Measure ANCOVA to control for age, gender, length of employment, and BMI, with effect sizes calculated using Cohen's d.Results: Significant reductions in MSDs complaints were observed across seven body regions (p